(untitled) (The Pretoria Student Law Review, 2021)
This special edition of the Pretoria Student Law Review (PSLR) is devoted to papers presented at a Conference on Decolonisation and Africanisation of Legal Education hosted by the University of Venda and the South African Law Deans Association (SALDA).1 This was the third event on decolonisation and Africanisation under the umbrella of SALDA in the period 2016 to 2019 and the first devoted to law students.